Management of Neurosurgical Patients During the COVID-19 Pandemic - Huaizhang Shi; Guang Yang; Cheng Gao; Xiaoxiong Wang; Guan Xin; Luan Rui; I. F. Gareev; O. A. Beylerli; Sh. Kh. Gantsev; Shiguang Zhao (Креативная хирургия и онкология)
The 2019 coronavirus infection (COVID-19) is a dangerous infectious disease proceeding as an acute respiratory viral infection with specific complications, which may include pneumonia leading to acute respiratory distress syndrome or respiratory failure with a high risk of death. The etiological agent of COVID-19 is a new coronavirus, referred to as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). This new viral form is most likely to have appeared from zoonotic coronaviruses, such as SARS-CoV emerged in 2002. This article sets out to present a strategy for manag‑ ing neurosurgical patients, which was developed taking into account the experience of the Neurosurgery Department of the First Affiliated Hospital of Harbin Medical University in the prevention and control of pneumonia outbreaks caused by the new coronavirus. This strategy can be helpful for neurosurgeons in providing emergency care in the context of the COVID-19 pandemic in the Russian Federation.